Educação dos pais versus obesidade infantil: o caso do município de Alexandria/RN - Diniz, Daniella Victória Mendes (Universidade Federal Rural do Semi-Árido, 2018)
This study aimed to investigate the role of maternal schooling on childhood obesity. In this sense, two empirical strategies on socioeconomic and family information of 204 children from the municipality of Alexandria located without a semi-arid region were adopted. The main results indicate that the higher the mother's education, on average, as children in general. In other words, the more educated they are as mothers the greater the likelihood of childhood obesity in children. This finding may be explained by the fact that more educated labor mothers and occupy more prominent positions in the labor market, and consequently with less money of dedication to family diets. In addition, it is believed that fast food food cultures are contributing in this direction. On the other hand, as an expo- sure, for variables considered of genetic effects, such as parental weight and father height.
Keywords: Obesidade infantil; Escolaridade da mãe; Fast food; Child obesity; Mother's education; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA